2004
DOI: 10.1002/elps.200406055
|View full text |Cite
|
Sign up to set email alerts
|

Charge density profiling of circulating human low‐density lipoprotein particles by capillary zone electrophoresis

Abstract: Capillary zone electrophoresis (CZE) has been utilized to profile the low-density (LDL) particles in human blood serum in this study. A 5 mM sodium phosphate buffer, pH 7.40, was chosen as the most suitable CE buffer and an extensive ultrafiltration (UF) procedure was applied to purify the LDL sample. Two LDL particle species, LDL with lower mobility and LDL- with higher mobility were observed. The electropherograms were highly reproducible with good precision of effective mobilities, corrected peak areas (CPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Eventually, lipoprotein fractions migrate with the EOF on the basis of their different particle charge density of mass. Liu et al [22] had demonstrated two LDL particles with significantly different charge/volume ratios based on their electrophoretic mobilities. Ceriotti et al [14] suggested that the microchip-based CE could be suited to distinguishing between different LDL types for certain diagnostic applications.…”
Section: Lipoprotein Fractional Peak Identificationmentioning
confidence: 99%
“…Eventually, lipoprotein fractions migrate with the EOF on the basis of their different particle charge density of mass. Liu et al [22] had demonstrated two LDL particles with significantly different charge/volume ratios based on their electrophoretic mobilities. Ceriotti et al [14] suggested that the microchip-based CE could be suited to distinguishing between different LDL types for certain diagnostic applications.…”
Section: Lipoprotein Fractional Peak Identificationmentioning
confidence: 99%
“…In addition, it was also observed that without ultrafiltration to clean the anticoagulants in LDL samples, the oxidation and glycation reactions were not successful. The optimal CE buffer chosen was 5 mM PB, pH 7.4, which was similar to that chosen in our previous study [18]. However, the mobilities and CE profiles observed in this study for native LDL particles are not exactly the same as that observed in the previous study.…”
Section: Search Of the Optimal Conditions For Ldl Sample Preparation mentioning
confidence: 68%
“…Recently, Liu difference of LDL isoforms and peak effective mobilities [18]. Liu et al has also used CZE to separate and determine in vitro oxidized phosphatidylcholine (PC) since PC is the most important phospholipids on LDL particles [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and coworkers demonstrated that capillary electrophoresis (CE) can be used to separate two LDL particles with significantly different charge/volume ratios given that the different ratios result in different electrophoretic mobilities [11]. Schmitz and coworkers developed a capillary isotachophoresis procedure for the separation of lipoproteins into 14 subclasses [12].…”
Section: Introductionmentioning
confidence: 99%